2010
DOI: 10.1007/s11274-010-0409-4
|View full text |Cite
|
Sign up to set email alerts
|

Bioemulsifier production by Aspergillus niger MYA 135: presumptive role of iron and phosphate on emulsifying ability

Abstract: Microbial emulsifiers are compounds employed in primary mechanisms for bioremediation of petroleum and other hydrocarbon pollutants from the environment. Although emulsifiers of biological origin are produced by microorganisms generally in response to growth on hydrocarbons, Aspergillus niger MYA 135 produced a bioemulsifier during fermentation in a sucrose-based culture medium at an initial pH of 5.0 and at 30°C. The production of bioemulsifiers can be strongly influenced by environmental factors. In this con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…On the contrary, the presence of FeCl 3 in a range of 0.5 - 10.0 mM impaired a NAGase purified extract activity (Pera et al 1997). Thus, as it was mentioned before, the addition of 1 g l -1 FeCl 3 to the BM encourages a scarcely branched mycelium and increases the production of both a mycelium-bound transesterification lipase activity (Colin et al 2011) and an emulsifier compound (Colin et al 2010a). Interestingly, in the same medium supplemented with 2% olive oil it was also observed that a specific extracellular hydrolytic lipase activity was increased by 6.6 fold after four days of incubation compared to the control (Colin et al 2010b).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…On the contrary, the presence of FeCl 3 in a range of 0.5 - 10.0 mM impaired a NAGase purified extract activity (Pera et al 1997). Thus, as it was mentioned before, the addition of 1 g l -1 FeCl 3 to the BM encourages a scarcely branched mycelium and increases the production of both a mycelium-bound transesterification lipase activity (Colin et al 2011) and an emulsifier compound (Colin et al 2010a). Interestingly, in the same medium supplemented with 2% olive oil it was also observed that a specific extracellular hydrolytic lipase activity was increased by 6.6 fold after four days of incubation compared to the control (Colin et al 2010b).…”
Section: Discussionmentioning
confidence: 87%
“…Interestingly, when A. niger MYA 135 grew mainly as dispersed mycelia the presence of an extracellular compound, if any, was only detected with electron microscope (data not shown). In addition, the production of an emulsifier activity was significantly increased (p < 0.05) under environmental conditions that support dispersed mycelial growth (Colin et al 2010a). Similarly, Prosser and Tough (1991) reported that the addition of nonionic surfactants, e.g., Span, to shake-flask cultures of A. niger also decreases spore aggregation thus allowing for dispersed growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The production of microbial emulsifiers, also called bioemulsifiers, has increased in recent years because of their higher biodegradability and reduced toxicity compared to their synthetically produced alternatives (Colin et al, 2010). Bioemulsifiers are amphiphatic molecules secreted by (micro)organisms, which facilitate the uptake of water-insoluble substrates (Shete et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…They are therefore commonly produced in response to microbial growth on hydrocarbons (Luna-Velasco et al, 2007;Martínez-Checa et al, 2007). However, there are also a few examples of bioemulsifier production during microbial growth on carbohydrates (Sarubbo et al, 2001;Colin et al, 2010).…”
Section: Introductionmentioning
confidence: 99%